OPTIMIZING OUTCOMES IN UNDISPLACED FEMORAL NECK FRACTURES AMONG ELDERLY PATIENTS: A NARRATIVE REVIEW. - Abhishek (Student's Journal of Health Research Africa, 2024)
Femoral neck fractures (FNF) in the elderly represent a formidable clinical challenge, often resulting from low-energy incidents such as falls. The increasing incidence of osteoporosis and other age-related diseases that negatively impact treatment outcomes adds to the complexity of addressing these injuries. The particular concern with undisplaced fractures lies in achieving fracture healing while minimizing the risk of complications such as non-union and avascular necrosis. The review aims to synthesize current evidence on the treatment modalities for undisplaced FNFs in elderly patients, focusing on optimizing union rates and minimalizing the risk of avascular necrosis, to guide clinical practice and policy development. The comprehensive review highlights the crucial role of early, tailored surgical intervention in promoting fracture healing. Internal fixation remains the ideal treatment for non-displaced fractures in patients with good bone healing potential, whereas hemiarthroplasty and total hip arthroplasty are favored in cases with a high risk of avascular necrosis or patients with pre-existing hip pathology. The significance of early postoperative rehabilitation and a multidisciplinary approach to care in enhancing recovery and functional outcomes is also emphasized. The insights gained underscore the need for further research into surgical innovations and rehabilitation strategies to improve outcomes for this vulnerable population. Future studies should aim at refining surgical techniques to reduce the incidence of complications and at developing comprehensive, patient-centered care plans. The findings advocate for the integration of multidisciplinary care pathways and personalized treatment plans in clinical policies to address the holistic needs of older patients with undisplaced FNFs. Such policies should emphasize the importance of rapid surgical intervention, where appropriate, and the early initiation of rehabilitation programs.